MENINGKATKAN DAYA SAING BISNIS UMKM STRATEGI ADAPTASI DI ERA DIGITAL - Sukandi, Pipin; Lisdayanti, Annisa; Hapsari, Ayuningtyas Yuli; Nilasari, Irma; Latifah, Ifa (Jurnal Abdimas Bina Bangsa, 2025)
This research aims to analyze and formulate adaptation strategies that can be applied by Micro, Small and Medium Enterprises (MSMEs) in increasing competitiveness in the digital era. Digital transformation has fundamentally changed the business competition landscape, so MSMEs need to adjust their strategies to be able to survive and grow. The research uses a training method with a case study approach on MSMEs under the auspices of a cooperative in the city of Bandung. Data collection was carried out through in-depth interviews, observations, and documentation studies. The results of the study show that effective adaptation strategies include: (1) Optimizing the use of digital platforms and social media for marketing and sales, (2) Developing an information technology-based management system to improve operational efficiency, (3) Improving human resource capabilities in mastering digital technology, (4) Implementing a business model that is more flexible and responsive to market changes, and (5) Building strategic collaboration with various stakeholders in the digital ecosystem. The implementation of this strategy has been proven to increase the competitiveness of MSMEs, which is reflected in increased sales, operational efficiency, and expansion of market reach. This research makes a practical contribution to MSME actors in formulating adaptation strategies in the digital era as well as theoretical contributions in the development of digital-based MSME business strategy models